The Development of Bulgarian-Greek Cultural Ties – Rhetorical Aspects of the Activity by the Association “Aristotle- A Cultural Bridge” - Medarska, Denitsa (Media and Language, 2020)
The following research focuses on the development of the cultural dialogue between Bulgaria and Greece through researching and analysing of virtual rhetoric and oratory in cultural meetings held by the association “Aristotle – cultural bridge”. The aim is to follow the rhetorical practices of this association, which serves as a cultural and spiritual centre, used in order to build a cultural bridge between the two countries. Moreover a bridge which serves as link for good ideas aimed at a common constructive collaboration between them. The conclusion at the end of this research is that any successful intercultural dialogue is a complicated process, which requires a wide range of rhetorical skills and techniques in order for each to effectively  breakthrough into the culture of the other. The mutual understanding and discovering of Bulgaria and Greece is done through the historical and contemporary societies in which the people of both nations form the multicultural plateau of the Balkans, with their language, habits and traditions.
Keywords: intercultural dialogue; „Aristotle-cultural bridge“; virtual rhetoric; rhetorical practices